2014
DOI: 10.1016/j.polymer.2014.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane foams based on crude glycerol-derived biopolyols: One-pot preparation of biopolyols with branched fatty acid ester chains and its effects on foam formation and properties

Abstract: Environmentally friendly biopolyols have been produced with crude glycerol as the sole feedstock using a one-pot thermochemical conversion process without the addition of extra catalysts and reagents. Structural features of these biopolyols were characterized by rheology analysis. Rigid polyurethane (PU) foams were obtained from these crude glycerol-based biopolyols and the foaming mechanism of the process was explored. Investigations revealed that partial carbonyl groups hydrogen-bonded with N-H were replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…These findings suggested that CG can be used to produce rigid/semi-rigid PU foams because the amount of hydroxyls for commercial polyols ranges from 34 mg KOH/g to 800 mg KOH/g. Li et al [136] rheologically analyzed and characterized CG-derived polyurethane foams. The results demonstrated that the branched FAE chains in the biopolyols are essential to reduce the degree of microphase separation and to stabilize bubbles during foaming processes.…”
Section: Polycondensation Polyestersmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that CG can be used to produce rigid/semi-rigid PU foams because the amount of hydroxyls for commercial polyols ranges from 34 mg KOH/g to 800 mg KOH/g. Li et al [136] rheologically analyzed and characterized CG-derived polyurethane foams. The results demonstrated that the branched FAE chains in the biopolyols are essential to reduce the degree of microphase separation and to stabilize bubbles during foaming processes.…”
Section: Polycondensation Polyestersmentioning
confidence: 99%
“…CG-based polyurethane foams exhibit potential applications. [134,136] No* ¼not feasible for the moment. The quality of CG is very subjective and is dependent on the type of derivatives; impurities of CG positively affect particular value-added chemicals.…”
Section: Process Products Feasibility Justificationmentioning
confidence: 99%
“…Also, foamed PU materials obtained with such biopolyols were produced, however investigation of their properties was often very limited and consisted only of basic mechanical testing [23,24]. More detailed analysis was performed by Li et al [25], although it did not include the evaluation of crude glycerolbased polyol's content in polyol mixture. Moreover, despite the fact that rigid PU foams are used mainly for thermal insulation, hardly any information can be found in the literature regarding the influence of crude glycerol-based polyols on thermal conductivity of rigid PU foams.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the applications of bioglycerol require the removal, at least, of the alkaline catalyst, through neutralization, and the separation of methanol . However, it is possible to take advantage of the impurities in bioglycerol for the cost‐effective production of some highly valuable products such as monoglycerides and polyols . Alkaline bioglycerol from biodiesel production has been used in the synthesis of soybean oil and castor oil‐based polyols through glycerolysis reaction, as reported by our group .…”
Section: Introductionmentioning
confidence: 92%
“…7 However, it is possible to take advantage of the impurities in bioglycerol for the cost-effective production of some highly valuable products such as monoglycerides and polyols. [8][9][10][11] Alkaline bioglycerol from biodiesel production has been used in the synthesis of soybean oil and castor oil-based polyols through glycerolysis reaction, as reported by our group. 12,13 These polyols were further converted into highly active unsaturated resins through maleinization reactions.…”
Section: Introductionmentioning
confidence: 99%